Śrīkr̥ṣṇayāmalamahātantram = Śrīkr̥ṣṇayāmalamahātantram : with the Jñānavatī Hindi commentary - Caturvedī, Rādheśyāma (Caukhambā Surabhāratī granthamālā, 2018)
Hindu tantric text on Krishna (Hindu deity)